2018
DOI: 10.1111/eos.12405
|View full text |Cite
|
Sign up to set email alerts
|

The immunopathogenic and immunomodulatory effects of interleukin‐12 in periodontal disease

Abstract: Interleukin 12 (IL-12) is an inflammatory cytokine that promotes the response of the immune system. This cytokine has been implicated as a potent stimulator of several diseases characterized by inflammatory-induced bone destruction, such as rheumatoid arthritis and periodontitis. Yet, the exact role of IL-12 in the development and progress of periodontitis has not been clarified. Several studies have demonstrated a positive correlation between the level of IL-12 and the severity of periodontal destruction. Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 105 publications
0
11
0
1
Order By: Relevance
“…Inflammation and immune response play key role in periodontal diseases such as gingivitis and periodontitis, which are considered to be the most common complications of diabetes (Karjalainen and Knuuttila, 1996 ). Additionally, the osteolytic role of the proinflammatory cytokine interleukin IL-12 was recently found to be involved in the pathogenesis of periodontal diseases (Issaranggun Na Ayuthaya et al, 2018 ). Differentially expressed proteins in these pathways, that could contribute to periodontal disease, are presented in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and immune response play key role in periodontal diseases such as gingivitis and periodontitis, which are considered to be the most common complications of diabetes (Karjalainen and Knuuttila, 1996 ). Additionally, the osteolytic role of the proinflammatory cytokine interleukin IL-12 was recently found to be involved in the pathogenesis of periodontal diseases (Issaranggun Na Ayuthaya et al, 2018 ). Differentially expressed proteins in these pathways, that could contribute to periodontal disease, are presented in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Garrido et al, (2018) reported that IFN-α induced the expression of ISG (at 6h post stimulation) by chicken macrophages to a greater extent than IFN-β (while IFN-β was a stronger inducer of pro-inflammatory cytokine gene expression (IL-1β, IL-6, and IL-8)). IL-12, produced by various immune cells (e.g., dendritic cells, macrophages, neutrophils), drives inflammatory Th1 responses, production of IFN-γ, and the cytotoxic activity of NK and CD8+ T cells (Issaranggun Na Ayuthaya et al, 2018). IL-17D is a member of the IL-17 family of cytokines produced by Th17 cells, is expressed in a wide range of tissues and organs, and stimulates the expression of IL-6 and IL-8 by various cells (Min et al, 2013).…”
Section: Interpretation Of Immune-related Gene Expression In Birds Momentioning
confidence: 99%
“…Both IL-12 and IL-35 share the same subunit, the IL-12p35 subunit, and belong to the IL-12 family. Recent studies have also reported that IL-12 could play both anti-inflammatory and proinflammatory roles depending on the different inflammatory microenvironment [ [11] , [12] , [13] ]. In the cardiovascular system, IL-22 could aggravate atherosclerosis via amplifying inflammation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%